In Vitro Evaluation of Wound Healing, Stemness Potentiation, Antioxidant Activity, and Phytochemical Profile of Cucurbita moschata Duchesne Fruit Pulp Ethanolic Extract - Preeyaporn Plaimee Phiboonchaiyanan; Saraporn Harikarnpakdee; Thanapat Songsak; Verisa Chowjarean (Hindawi Limited, 2024)
Wound healing comprises an intricate process to repair damaged tissue. Research on plant extracts with properties to expedite wound healing has been of interest, particularly their ability to enhance the stemness of keratinocyte stem cells. Hence, the present study aims to determine the wound healing and stemness potentiation properties of an ethanolic extract derived from Cucurbita moschata fruit pulp (PKE). Human keratinocytes (HaCaT) and primary skin fibroblast cells were used in this study. The migration of the cells was examined by using a scratch wound healing assay, and spheroid behavior was determined by using a spheroid formation assay. The proteins related to migration and stemness were further measured by using Western blotting to explore the mechanism of action of PKE. The methods used to evaluate PKE's antioxidant properties were 2,2-diphenyl-2-picrylhydrazyl (DPPH) scavenging, ABTS radical scavenging activity, and superoxide anion radical scavenging (SOSA) assays. The phytochemistry of the PKE was investigated using phytochemical screening and high-performance liquid chromatography (HPLC) analysis. The results of this study indicate that nontoxic concentrations of PKE increase the rate of migration and spheroid formation. Mechanistically, PKE increased the expression of the migratory-related protein active FAK (phosphorylated FAK), and the subsequence increased the level of p-AKT. The expression of stem cell marker CD133, upstream protein signaling β-catenin, and self-renewal transcription factor Nanog was increased. The PKE also possessed scavenging properties against DPPH, ABTS, and SOSA. The phytochemistry analyses exhibited the presence of alkaloids, glycosides, xanthones, triterpenes, and steroids. Additionally, bioactive compounds such as ɑ-tocopherol, riboflavin, protocatechuic acid, β-carotene, and luteolin were detected. The presence of these chemicals in PKE may contribute to its antioxidant, stem cell potentiation, and wound-healing effects. The findings could be beneficial in the identification of valuable natural resources that possess the capacity to be used in the process of wound healing through the potentiation of stemness via a readily detectable molecular mechanism.